Implementasi Pendidikan Inklusi Terhadap Pembelajaran Anak Berkebutuhan Khusus Di MAN 2 Kota Payakumbuh - Tiara Yulia Putri; Khairatul Zahra; Kharisma Hakim (LPPM Politeknik Pratama, 2023)
The implementation of the inclusion education in Madrasah Aliyah Negeri (MAN) 2 of Payakumbuh City is given to students who experience special needs, The existence of this education makes MAN 2 Payakumbuh City as the Child Friendly School 2 Payakumbuh City was selected as the